Censorship detected in TZ (Tanzania) - Voidly (2025)
CRITICAL severity censorship detected in Tanzania. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: TZ-2025-0002
Keywords: censorship; TZ; censorship; critical